Understanding the Revenue Structure of Municipalities in the Context of Achieving Sustainable Development - Mohammad-Reza Daroudi, Sania Sami (International Journal of Scientific Research and Management (IJSRM), 2017)
In general, the main issue that all municipalities seek in scope of revenue is creating a systemized and integrated structure that can lead to gaining sustainable earning for municipality. New attitude of urban management at the world would not seek only to find contexts to gain required earning, but also sustainability of revenue sources or desirability of the sources is prior. Hence, sustainability of revenues is depended on this issue that the accruals can have relative continuity and secondly, such revenue should not threaten the qualitative conditions of city. Hence, achieving to new methods of supplying sustainable revenue sources and without bad economic, social and political outcomes plays vital role in satisfaction of urban community, acceleration of development and construction of urban areas and finally, desirable urban management. Status of municipalities of the country can't also be an exception and dominant attitude to achieving new sources and modification of existing sources should move toward reliance on sustainable revenues and going away from unsustainable revenues. In this study, first of all after a short review of theoretical concepts and sources of revenue of municipalities and urban sustainable economy, dynamic and sustainable revenue structure is investigated and after that, proposed model for sustainable revenues of municipalities is presented. Finally, the conditions for realization and prerequisites of sustainability of favorable revenue are evaluated.